Pandangan Islam Mengenai Surat Kuasa Profesi Advokat dengan Al-Wakalah Ditinjau dari Ayat-Ayat Al-Qur’an dan Hadis - Denni Herdiansyah; Muhammad Royhan; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Indonesia as a state of law based on Pancasila and the constitution of the Republic of Indonesia year 1945, Indonesia is a country with a majority Muslim population, which makes Islam dominant in governing its people in every line of life It includes the teachings of truth, honesty, and justice that a person of law enforcement in Indonesia must possess. Advocate is one of the professions of law enforcement in Indonesia that have dedicated itself to the interests of the community and have contributed to the establishment of justice and truth. so the advocate profession has been called the “Officium Nobile